Analisis Dampak Fear of Missing Out (FOMO) terhadap Minat Beli Skintifict yang Viral di TikTok oleh Generasi Z E-Commerce Users - Nabila Tsabitha Saptaningtyas; Rossa Ardanella; Nandha Narendra Muvano (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
The development of short-form video-based social media, particularly TikTok, has transformed Generation Z's consumption behavior, particularly in the skincare industry. One phenomenon that has emerged due to intense exposure to viral content is Fear of Missing Out (FoMO), a fear of missing out on trends that drives consumers to make quick and impulsive purchases. This study aims to analyze the impact of FoMO on purchase intention for Skintific skincare products that went viral on TikTok among Generation Z e-commerce users. The research method used was a Systematic Literature Review (SLR), analyzing and synthesizing various journals and scientific articles relevant to the topics of FoMO, TikTok, Generation Z consumption behavior, and e-commerce. Data analysis techniques used narrative and thematic synthesis to identify patterns, similarities, and differences in previous research findings. The results show that FoMO plays a key psychological role in bridging the influence of TikTok viral marketing on Skintific purchase intention. Review content, before-and-after content, user testimonials, and beauty influencer recommendations shape perceptions of popularity and urgency that drive Generation Z purchasing decisions. TikTok's integration with e-commerce platforms further strengthens FoMO through promotional features and ease of transaction. This research contributes to enriching the study of digital consumer behavior and provides practical implications for skincare brands, e-commerce platforms, and Generation Z consumers in navigating the phenomenon of social media-based marketing.